EXPLORING MOTIVATIONS FOR ONLINE VOLUNTEERING IN EMERGING ADULTS: A DESCRIPTIVE STUDY - Ramadhia, Ulfah; Arfensia, Danny Sanjaya (Psychosophia: Journal of Psychology, Religion, and Humanity, 2023)
The widespread use of the internet has led to a new activity involving individuals in spreading goodness through voluntary social engagement. This activity is known as online volunteering. The flexible nature of online volunteering has increased interest and enthusiasm, particularly among emerging adults, motivating them to participate in such activities. However, research on this phenomenon, especially among emerging adults, is still limited. This study aims to explore the various forms of motivation among emerging adults to participate in online volunteering. A total of 205 emerging adult participants who have previously or are currently engaged in online volunteering activities are recruited to complete the Volunteer Functions Inventory adaptation scale. Descriptive analysis indicates that out of the six proposed motivation forms, Motivations related to understanding, values, and enhancement play a crucial role in motivating emerging adults to engage in online volunteering. These three motivational factors serve as the primary incentives for emerging adults to develop themselves and achieve their goals. Additionally, the study finds that emerging adults who engage in online volunteering activities for 6 months to 1 year and those who participate in environmental online volunteering exhibit higher motivation compared to those engaged in volunteering for longer durations and in other volunteer fields. Overall, this research identifies a high level of motivation among emerging adults participating in online volunteering activities, categorizing it as a significant driving factor.